RELASI SOSIAL EKONOMI WARUNG REMANG-REMANG DI PERKEBUNAN KELAPA SAWIT DESA DAYUN KECAMATAN DAYUN KABUPATEN SIAK - Risda Marita Br. H; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Prostitution is a social gap or social problem that influences the development of morals and order of values in society. A dimly-lit stall is one form of covert prostitution in Dayun Village and not something new to hear. The existence of this dimly lit stall is indeed disturbing residents, because it damages the image of the village and is not in accordance with the norms prevailing in the community. This practice site is small houses that are open every day starting from the afternoon until the night or even at 3 in the morning. These waiters (prostitutes) will accompany customers who come to drink, and then lead to sex transactions. And accompanied by music that is very noisy in the ear and the music is heard from a distance. The technique of determining informants in this study was using purposive sampling. The research method used is descriptive qualitative research method. The theory used is the theory of structural functionalism and social capital consisting of social networks, trust, and social norms and values. The results of the study can be concluded that the average sex worker who works in this dimly lit stall has a low educational background and is already a widow. Many of the sex workers who work in these places are not immune from economic reasons. This makes them forced to work as sex workers. They also do not have extensive social relations (relations) in achieving economic goals. Doing their own activities or businesses without having to deal with their rival stalls.     Keywords:  Dimly-it Stall, Social Capital, and Socio-economic Relations